2015
DOI: 10.1021/acs.jproteome.5b00375
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Portrait of Breast-Cancer-Derived Cell Lines Reveals Poor Similarity with Tumors

Abstract: Breast-cancer-derived cell lines are an important sample source for cancer proteomics and can be classified on the basis of transcriptomic analysis into subgroups corresponding to the molecular subtypes observed in mammary tumors. This study describes a tridimensional fractionation method that allows high sequence coverage and proteome-wide estimation of protein expression levels. This workflow has been used to conduct an in-depth quantitative proteomic survey of five breast cancer cell lines matching all majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, the heterogeneity of all the cell types found in patient tumors cannot be replicated using cell lines. A higher level of amplification and a differential protein expression pattern compared to primary tumor cells has also been observed in breast cancer cell lines, one explanation might be the source of the cells which is mainly from pleural effusions or triple negative primary cancer [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterogeneity of all the cell types found in patient tumors cannot be replicated using cell lines. A higher level of amplification and a differential protein expression pattern compared to primary tumor cells has also been observed in breast cancer cell lines, one explanation might be the source of the cells which is mainly from pleural effusions or triple negative primary cancer [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although immortalized cellular models provide invaluable knowledge regarding cancer biology and drug effects on cellular systems, they are limited in their inability to re-create essential features of tumors. More speci cally, these models cannot accurately re ect the tumor architecture, three-dimensional structure and alignment of tumor cells, matrix, and surrounding stroma, and cannot reproduce the cellular heterogeneity that is present in the original patient tumor [36][37][38][39] . Conversely, orthotopic xenograft models recapitulate the complexity of tumors, but the inability to scale these models limits their use in large drug screens.…”
Section: Discussionmentioning
confidence: 99%
“…models acquire irreversible genetic and behavioral changes upon serial passaging (6,7). Such pre-clinical models also lack stromal elements that are unable to mirror the architecture and heterogeneity of human tumors (7)(8)(9). Guo et al (10) have reported poor cancer type specificity in cancer cell lines, suggesting that they deviate both histologically, pathologically and molecularly from patient tumors.…”
Section: Development and Characterization Of A Patient-derived Orthot...mentioning
confidence: 99%